Why Stress Remains an Ambiguous Concept: Reply to McEwen & McEwen (2016) and Cohen et al. (2016). (July 2016) - Kagan, Jerome
This reply to the commentaries by Cohen, Giannaros, and Manuck (2016, this issue) and McEwen and McEwen (2016, this issue) acknowledges investigators' reluctance to relinquish the term stress, despite the lack of agreement on its meaning and the evidence that is a sign of its presence. This brief reply urges scientists studying the exemplars of this ambiguous concept to search for robust relations that specify the type of event, the properties of the agent, the agent's circumstances, and the behavioral or biological consequences. The accumulation of these relations will reveal that the word stress adds little to our understanding.